Strategic management in emerging markets : aligning business and corporate strategy - Todorov, Krasimir; Akbar, Yusaf H., 1969- (Emerald Publishing Limited, 2018)
Traditionally, analysis of strategic management has divided the focus between a business and corporate level. This text goes beyond that to help readers recognize the interplay of the "how" and "which" of strategy. It embraces the integrated nature of learning to avoid the compartmentalization of strategy concepts.'Strategic Management in Emerging Markets: Aligning Business and Corporate Strategy' has three uniquely valuable components. First, it identifies and integrates corporate and business strategy levels along with their co-evolution; enabling readers to better understand strategic alignment. Secondly, there is an explicit presentation of strategy for emerging markets which utilizes original theory and cases to help readers to better identify and succeed in high growth business contexts. Thirdly, it presents an integrative and comprehensive case study of an international corporation, Inchcape Inc., which is designed specifically to facilitate cumulative and holistic learning.The book focuses on newer aspects of strategy theory and the hallmarks of emerging markets, such as dynamic capabilities, environmental turbulence, and the difficulties associated with strategic choice and execution in complex business environments. An appreciation of the role of megatrends is also a key aspect since emerging markets evolve at much faster rates than slower growth developed economies. Appealing to practitioners and students of strategic management and international business, the book bridges conceptual and practical realms of strategy generating intellectual synergies for the reader and enhancing the learning experience.
Keywords: Strategic planning.; Business planning.; Industrial management -- Developing countries.; Business & Economics -- General.; Economics, finance, business & management.; elektronické knihy; electronic books